Anticoagulant regimens for different therapeutic plasma exchange modes - Yao, Ruishan; Huang, Haiyan; Ming, Yaohui; Guo, Huiling; Miao, Lingli; Wang, Su; Wan, Jia; Zhou, Jin; Wang, Xiaofang; Wu, Yanli; Yuan, Yaowen; Wang, Ting; et al. (Frontiers in Medicine, 2025)
Therapeutic plasma exchange (TPE) is widely used in various fields of clinical practice. There are two main modes of TPE: centrifugal TPE (cTPE) and membrane TPE (mTPE). No matter which mode of TPE, anticoagulant therapy is essential to prevent clotting in the extracorporeal circuit. Therefore, selecting a suitable and safe anticoagulant is crucial. Currently, heparin and citrate are the most commonly used anticoagulants. Different anticoagulant regimens have varying advantages, disadvantages, and associated complications, making them suitable for different TPE modes. This review aims to summarize relevant research findings to provide clinicians with evidence to guide their selection of appropriate anticoagulants during TPE.